KEBIJAKAN PEMERINTAH INDONESIA MENGURANGI EKSPOR MINERAL MENTAH KE JEPANG SETELAH PEMBERLAKUAN UNDANG-UNDANG MINERBA NO 4 TAHUN 2009 - fitri Sanjaya; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses the Indonesian government policies reduce raw mineral exports toJapan, after the enactment of legislation number 4 of 2009. Mining policy has causedconsiderable turmoil serious, many stakeholders in the mining sector who do not agree with thispolicy among Japanese and mining companies in Indonesia. This policy is difficult to acceptbecause it is considered to be difficult and hurt the company. To discuss the problem of mineralexport policies Indonesia using qualitative research methodology explanative, where datacollection using literature data collection techniques (library research) derived from sources inthe form of literature (books), periodicals such as newspapers, magazines, journals, andscientific articles. In discussing the problem of mineral export policies used foreign policy theoryRichard Snayder for more in-depth look at the measures taken by the Indonesian government.Reduction policies raw mineral exports to Japan by Indonesia because the Indonesiangovernment will develop downstream mining sector by processing and refining of minerals in thecountry, and reduce the export of raw mineral raw materials in order to meet domestic mineralprocessing. The policy is a step to improve the national development.Keywords: Law And Coal, Mineral Export Policies, Downstream Mining, Nickel